Conceptualization of Limit Theory as an Epistemological Instrument for Renewal of Interpretation in the Thoughts of Fazlur Rahman and Abdul Aziz - Yunus Hawary; Andri Nirwana. AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to construct and analyze the theory of limits as an epistemological instrument for interpretive renewal in the thought of Fazlur Rahman and Abdul Aziz. The primary focus of this study is to understand how these two figures place the limits of rationality and the authority of revelation in the process of interpreting the Qur'an. This study uses a qualitative approach with library research and applies a philosophical-hermeneutic approach. Data were obtained from the main works of Fazlur Rahman (Islam and Modernity, Major Themes of the Qur'an) and Abdul Aziz (Limit Theory in Islamic Epistemology, Contemporary Islamic Epistemological Reform), then analyzed using content analysis with a comparative-critical approach. The results show that Fazlur Rahman emphasizes limits as the moral boundaries of the Qur'an that keep interpretation rooted in the values of revelation, while Abdul Aziz formulates limits as an epistemic framework that regulates the extent to which rationality can play a role in interpreting divine texts. The two combine to form a conceptual synthesis that suggests that limit theory serves as an epistemological balancing mechanism between freedom of thought and adherence to revelation. This research contributes to strengthening the epistemological aspect of exegetical methodology and offers a sustainable paradigm of exegesis (afsir) that is rational, contextual, and maintains divine value.